Contributions of Basal and Prandial Hyperglycemia to Total Hyperglycemia in Older and Younger Adults with Type 2 Diabetes Mellitus. Issue 4 (21st March 2013) - Munshi, Medha N.; Pandya, Naushira; Umpierrez, Guillermo E.; DiGenio, Andres; Zhou, Rong; Riddle, Matthew C.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the relative contributions of basal and prandial components to total hyperglycemia in older and younger adults with type 2 diabetes mellitus. Design Participant‐level data were pooled from six randomized studies of 24 weeks or longer treatment with insulin glargine or an active comparator. Setting Prospective, randomized Phase 3 or 4 controlled trials. Participants One thousand six hundred ninety‐nine individuals: 509 (30%) aged 65 and older and 1, 190 (70%) younger than 65. Measurements Contributions of basal hyperglycemia (BHG) and postprandial hyperglycemia (PPHG) to total hyperglycemia, defined as the incremental area under the curve of daytime blood glucose (BG) from the overall glucose profile calculated from 7‐point self‐measured BG profiles, of participants aged 65 and older were compared with those of participants younger than 65. Results After 24 weeks of treatment, glycosylated hemoglobin (HbA1c) decreased in the older (8.6–7.0%) and younger (8.7–7.1%) groups; the relative contribution of BHG was significantly lower in both age groups (P < .001). The relative contribution of BHG to that of PPHG was significantly smaller in older than in younger participants at baseline (75.4% vs 79.4%; P < .001) and 24 weeks (37.6% vs 44.7%; P < .001). The relative contribution of BHG to total hyperglycemia was not correlated with HbA1c at baseline and after 24 weeks of treatment in older participants but was positively correlated at baseline (correlation coefficient (r) = 0.082; P = .005) and 24 weeks (r = 0.062; P = .03) in younger participants. A significantly lower proportion of older participants reported symptomatic, glucose‐confirmed, and nocturnal hypoglycemia during 24 weeks of treatment (P < .001). Conclusion The relative contribution of BHG was lower, and that of PPHG was greater in older than in younger participants, suggesting that different therapeutic approaches may be required to treat hyperglycemia effectively in these different age groups.